Methods for finding differential characteristics of block cipher «Cypress» - Rodinko, M.Yu.; Oliynykov, R.V. (Radiotekhnika, 2017)
Three methods for finding differential characteristics of the round function of the block cipher «Cypress» are proposed, namely: a direct search method, a two-way search method, and an optimized method for finding the differential characteristic with high probability. The purpose of all three approaches is to activate the smallest amount of bits at inputs of the modulo addition transformation of the round function, which, in turn, increases the likelihood of the transformation. The optimized method makes it possible to find the differential characteristic on the round function of the block cipher "Cypress" with a probability that equals ¼.